Raymond Williams and the possibilities of ‘committed’ late Marxism - Stevenson, Nick (Raymond Williams Society, 2018)
After the end of the Cold War Marxist thought entered into a long crisis from which it is only just beginning to emerge. After 1989 it was no longer clear, apart from a few revolutionary outposts, what a commitment to Marxism meant. Not surprisingly a generation of intellectuals who had previously called themselves Marxists either abandoned a relationship to revolutionary ideals or very quickly affixed a prefix to make Post-Marxism. Marxism was charged with being intrinsically authoritarian, statist and hierarchical in the way it sought to manage the economy and wider society. These features remain a powerful strain within Marxism: many groups on the revolutionary Left survive as hierarchical organisations wedded to ideas from a more insurrectionary political period. Yet there remain alternative configurations of Marxism capable of reinventing themselves in the context of the present. A widely read collection of essays, quickly issued by Verso after the fall of the Berlin Wall, featured Jurgen Habermas. One of the European Left’s leading intellectuals, Habermas argued that socialists need to give up ideas of overthrowing the system and focus instead upon moral and cultural concerns. Socialism became less about questions of ownership and control and more concerned with the redistribution of power through democratic means, as Left debate sought to reinvent social democracy for the emergent global age. The old model of socialism stood accused of seeking to capture state power, leading to the eventual subordination of civil society. However Raymond Williams, and the New Left more generally, had long been critical of the kinds of Leninist transformation that Habermas depicted. Williams had his own ambivalences around the term Marxist, but generally seemed to feel that it articulated a complex tradition of thought that had been significant in the formation of the New Left. However, unlike many others who remained connected to Marxism, Williams was engaged in a careful exercise in re-thinking what this legacy might come to mean in the future.